Metabolic reprogramming orchestrates cancer stem cell properties in nasopharyngeal carcinoma - Shen, Yao-An (Cell Cycle, 2014)
Cancer stem cells (CSCs) represent a subpopulation of tumor cells endowed with self-renewal capacity and are considered as an underlying cause of tumor recurrence and metastasis. The metabolic signatures of CSCs and the mechanisms involved in the regulation of their stem cell-like properties still remain elusive. We utilized nasopharyngeal carcinoma (NPC) CSCs as a model to dissect their metabolic signatures and found that CSCs underwent metabolic shift and mitochondrial resetting distinguished from their differentiated counterparts. In metabolic shift, CSCs showed a greater reliance on glycolysis for energy supply compared with the parental cells. In mitochondrial resetting, the quantity and function of mitochondria of CSCs were modulated by the biogenesis of the organelles, and the round-shaped mitochondria were distributed in a peri-nuclear manner similar to those seen in the stem cells. In addition, we blocked the glycolytic pathway, increased the ROS levels, and depolarized mitochondrial membranes of CSCs, respectively, and examined the effects of these metabolic factors on CSC properties. Intriguingly, the properties of CSCs were curbed when we redirected the quintessential metabolic reprogramming, which indicates that the plasticity of energy metabolism regulated the balance between acquisition and loss of the stemness status. Taken together, we suggest that metabolic reprogramming is critical for CSCs to sustain self-renewal, deter from differentiation and enhance the antioxidant defense mechanism. Characterization of metabolic reprogramming governing CSC properties is paramount to the design of novel therapeutic strategies through metabolic intervention of CSCs.